2016
DOI: 10.1186/s12883-016-0619-y
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory tests as short-term correlates of stroke

Abstract: BackgroundThe widespread adoption of electronic health records provides new opportunities to better predict which patients are likely to suffer a stroke. Using electronic health records, we assessed the correlation of different laboratory tests to future occurrences of a stroke.MethodsWe examined the electronic health records of 2.4 million people over a two year time span. These records contained 26,964 diagnoses of stroke. Using Cox regression analysis, we measured whether any one of 1796 different laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Neutrophils are, therefore, also of considerable importance as targets for treating and preventing ischemic stroke [ 29 ]. A study by Sughrue et al [ 10 ] produced results similar to ours regarding the positive association between neutrophils and stroke occurrence. Hemoglobin levels can predict the risk of stroke.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Neutrophils are, therefore, also of considerable importance as targets for treating and preventing ischemic stroke [ 29 ]. A study by Sughrue et al [ 10 ] produced results similar to ours regarding the positive association between neutrophils and stroke occurrence. Hemoglobin levels can predict the risk of stroke.…”
Section: Discussionsupporting
confidence: 87%
“…There have been no studies suggesting that lymphocyte percentage can be a predictor of stroke, but different studies have examined the use of immune cells as biomarkers to predict stroke outcome [ 26 , 27 ]. There is one study that showed a negative correlation between hematocrit and stroke occurrence [ 10 ]. Folate deficiency has various clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Zhao et al (2018) has shown that higher levels of HDL are associated with decreased risk of stroke, but some studies have suggested that higher levels of total cholesterol, HDL, LDL, and non-HDL cholesterol significantly decrease the incidence of stroke. They have also explained that higher levels of non-HDL cholesterol can be a significant risk factor for the cardiac disease but not necessarily for stroke (Gordon et al, 1977;Sughrue et al, 2016). This can describe that cardiac disease could cause a higher mortality rate in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Mann–Whitney U test or t ‐test was utilized for differences between groups of continuous variables, and the χ 2 test or Fisher's exact test was applied for categorical variables. Compared to serum creatinine levels, eGFR was more suitable for evaluating renal function 17 . Therefore, eGFR was used for developing the model to avoid multicollinearity and improve its performance.…”
Section: Methodsmentioning
confidence: 99%